Electrochemical Analyses of Carbon Nanotube Based Supercapacitor in 1M LiPF6 Organic Electrolyte - Mohd Abid, Mohd Asyadi Azam; Rosle, Muhammad Firdaus (2013)
Excellent electrical conductivity, high mesoporosity, and high electrolyte accessibility of carbon nanotube (CNT) ensure a high charge transport capability and hence a high power density for the capacitor. However, performance of the supercapacitors should be improved to satisfy the increasing demands for various applications. In this article, commercial CNT was used as active material and a non-aqueous solution, LiPF6 was used as electrolyte to fabricate electrodes for EDLC-type supercapacitor. Electrochemical measurements such as BET analysis and cyclic voltammetry were performed to determine the capacitance behavior of the device. As results, specific surface area of the CNTs was found to be 609 m2 g-1, and specific capacitance was calculated to be 42 F g-1.